Numerical models and ductile ultimate deformation response of post-tensioned self-centering moment connections. - Kim, Hyung-Joon
New steel moment-resisting connections that incorporate post-tensioning elements to provide a self-centering capacity and devices to dissipate seismic input energy have recently been proposed and experimentally validated. Experimental studies have confirmed that these connections are capable of undergoing large lateral deformations with negligible residual drifts. To facilitate their implementation, accurate modeling of the behavior of systems incorporating post-tensioned connections must be readily available to designers and researchers. A number of simplified models have been suggested in the literature by researchers trying to capture experimental results at the beam?column connections and thereby to predict the global response of structures incorporating such connections. To provide a clear set of guidelines for the modeling of post-tensioned steel frames, for practicing engineers as well as researchers, in this paper three types of numerical models of increasing complexity are presented: (i) a sectional analysis procedure, (ii) a lumped plasticity spring frame leveled approach and (iii) a non-linear solid finite element analysis to predict the response at ultimate deformation levels. The analytical results obtained from the numerical models predict well the structural behavior of these connections when compared with available experimental data. Even at the ultimate deformation level, analytical results are in good agreement with test results. Furthermore, detailing requirements are proposed to assure that flexural hinges form in the beams in order to improve the cyclic response of steel self-centering connections when drifts exceeding the design drifts are imposed to the system. Experimental and analytical studies demonstrate that steel post-tensioned self-centering connections incorporating the proposed detailing in the beams develop an increased deformation capacity and thereby exhibit a ductile response while avoiding a sudden loss of their strength and stiffness.
Keywords: Post-tension.; Self-centering.; Energy dissipating devices; Numerical models; Flexural hinges